The Sharia Compliance Analysis of the Mudharabah Contract at PT Permodalan Nasional Madani Mekaar Syariah - Wulandari, Putri; Nasik, Khoirun (MALIA: Jurnal Ekonomi Islam, 2023)
Financial institutions in Islam are governed by rules of halal (permissible) and haram (forbidden). One example of an Islamic financial institution is PNM Mekaar Syariah, which operates under various Sharia contracts. To ensure its Sharia compliance, it is necessary to analyze its pillars, conditions, and mechanisms. The objective of this research is to examine the Sharia compliance of the Mudharabah contract used in capital financing at PNM Mekaar Syariah, focusing on the branch in Prambon. This study adopts a qualitative descriptive approach. The findings reveal that PT PNM Mekaar offers Sharia-compliant capital financing products, as demonstrated by the research findings on the practice of capital provision by PNM Mekaar Syariah to its customers. However, there are some pillars and conditions that do not align with Sharia principles, leading to the deterioration of the Mudharabah contract's validity.